Natural dipeptidyl peptidase-IV inhibitor mangiferin mitigates diabetes- and metabolic syndrome-induced changes in experimental rats - Suman RK (Dove Medical Press, 2016)
Rajesh Kumar Suman,1 Ipseeta Ray Mohanty,1 Ujwala Maheshwari,2 Manjusha K Borde,1 YA Deshmukh1 1Department of Pharmacology, 2Department of Pathology, MGM Medical College, Kamothe, Navi Mumbai, India Background: Mangiferin (MNG) is known to possess antidiabetic and antioxidant activity. However, there is no experimental evidence presently available in the literature with regard to its ameliorating effects on diabetes mellitus coexisting with metabolic syndrome.Objective: The present study was designed to evaluate the protective effects of MNG on various components of metabolic syndrome with diabetes as an essential component.Material and methods: Adult Wistar rats were fed high-fat diets for 10 weeks and challenged with streptozotocin (40 mg/kg) at week three (high-fat diabetic control group). After the confirmation of metabolic syndrome in the setting of diabetes, MNG 40 mg/kg was orally fed to these rats from the fourth to tenth week.Results: The treatment with MNG showed beneficial effects on various components of metabolic syndrome, such as reduced dyslipidemia (decreased triglyceride, total cholesterol, low-density lipoprotein cholesterol, and increased high-density lipoprotein cholesterol) and diabetes mellitus (reduced blood glucose and glycosylated hemoglobin). In addition, an increase in serum insulin, C-peptide, and homeostasis model assessment-β and a reduction in homeostasis model assessment of insulin resistance-IR were observed in MNG-treated group compared with high-fat diabetic control group. MNG was also found to be cardioprotective (reduction in creatine phosphokinase-MB levels, atherogenic index, high-sensitivity C-reactive protein). Reduction in serum dipeptidyl peptidase--IV levels in the MNG-treated group correlated with improvement in insulin resistance and enhanced β-cell function.Conclusion: The present study has demonstrated antidiabetic, hypolipidemic, and cardioprotective effects of MNG in the setting of diabetes with metabolic syndrome. Thus, MNG has the potential to be developed as a natural alternative to synthetic dipeptidyl peptidase-IV inhibitors beneficial in this comorbid condition. Keywords: mangiferin, diabetes, metabolic syndrome, high-fat diet, streptozotocin, rats